OPTIMIZATION OF REGENERATION AND AGROBACTERIUM MEDIATED TRANSFORMATION OF SUGAR BEET (Beta vulgaris L.) - Baloğlu, Mehmet Cengiz (My University, 2005)
In this study, optimization of a transformation and regeneration system via indirect and direct organogenesis in cotyledon, hypocotyl, petiole, leaf and shoot base tissues of sugar beet (Beta vulgaris L. cv. ELK 345 and 1195) was investigated. Two different germination, three different callus induction and shoot induction medium was used for indirect organogenesis of sugar beet cultivar ELK 345. Except cotyledon, other explants (hypocotyl, petiole and leaf) produced callus. However no shoot development was observed from callus of these explants. Shoot base tissue of sugar beet cultivar 1195 was employed for direct organogenesis. Shoot development was achieved via direct organogenesis using 0.1 mg/L IBA and 0.25 mg/L BA. Root development and high acclimatization rate were accomplished from shoot base tissue.
ŞEKER PANCARINDA (Beta vulgaris L.) REJENERASYON VE AGROBAKTERİYE DAYALI TRANSFORMASYONUN OPTİMİZASYONU
Keywords: Sugar beet, indirect organogenesis, direct organogenesis, shoot base; Şeker pancarı, indirekt organogenesis, direct organogenesis